PENGARUH KOMPETENSI MANAJERIAL KEPALA SEKOLAH DAN MOTIVASI KERJA GURU TERHADAP KINERJA GURU SD WILAYAH GUGUS 2 KECAMATAN BATULANTEH - USMAN USMAN; MUHAMMAD IKHSAN; RUSMIN NURJADIN (GANEC SWARA, 2024)
The objectives of this research are 1) to analyze the influence of the managerial competence of school principals on the performance of elementary school teachers in Cluster 2 of Batulanteh District, 2) to analyze the influence of the work motivation of teachers on the performance of elementary school teachers in Cluster 2 of Batulanteh District, and 3) to analyze the influence of the managerial competence of school principals and the work motivation of teachers on the performance of elementary school teachers in Cluster 2 of Batulanteh District. This research is designed using a non-experimental quantitative approach. The research population includes all school principals and teachers of SDN Tangkampulit, SDN Tepal, SDN Baodesa, SDN Sukamaju, SDN Batubara, and SDN Sampar Kuang Rea, totaling 60 people. The research sample consists of 60 people selected using non-random sampling, specifically saturation sampling, often called a census. Data collection procedures include observation, questionnaires, and documentation. Data analysis techniques involve hypothesis testing, t-test, ANOVA, and simple linear regression. The research findings indicate that the managerial competence of school principals has a significant influence on the performance of elementary school teachers in Cluster 2 with a t-value of 4.703 > t-table 1.66. The correlation between the managerial competence of school principals and the performance of teachers is 0.525, categorized as moderate. Similarly, the influence of work motivation on the performance of teachers is significant with a t-value of 4.593 > t-table 1.66. The correlation between work motivation and teacher performance is 0.516, categorized as moderate. Furthermore, the combined influence of managerial competence and work motivation on teacher performance is significant with an F-value of 10.918 > F-table 3.158 at a significance level of 0.000 < 0.05. Therefore, it can be concluded that both the managerial competence of school principals (X1) and the work motivation of teachers (X2) simultaneously have a significant impact on the performance of elementary school teachers (Y) in the Cluster 2 area.